Tryumf Taidy ogłoszony. O diariuszu obłóczyn u dominikanek lwowskich księżnej Teofili Wiśniowieckiej w 1753 roku - Kuran, Michał (Wydawnictwo Uniwersytetu Rzeszowskiego, 2014)
The article presents the structure and main themes of the diary of the solemn investiture ceremony of Teofila Wiśniowiecka entitled "Tryumf troistej Łaski Boskiej" [“The Triumph of the Threefold Divine Grace”] from 1753. This literary work is presented against the background of monastic customs which accompany the investiture. Introduction of many persons served to commemorate their role in the ceremony and to praise the families they represented. The article describes the activities presented in the diary to announce the celebrations. The course of the events is pointed out considering the role of decorations which were especially stressed in the diary. The interior decorated with not only expensive materials and costly votive offerings but also flowers, which were appropriately lit, was accompanied by Baroque splendor with processional marches, the firing of cannons and the music performed by the duke’s band. Theatralization of the event is emphasized. The article considers the rhetorical structure of the speeches included in the diary (dispositio) and the main themes from the sphere of inventio. It also shows which elements of the event were not included in the diary. They were omitted because they did not comply with the rules of the ceremony (i.e. lack of secular speeches during the act of investiture). The investiture was shown as a special case of a rite of passage because it was a doyenne of the family who was joining the Order, not a young maiden. The act was important because while she was still alive she left inheritance to her descendants who felt obliged to pay tribute to her. The Order also accepted her with due respect as their protector and founder. Publication of the diary was intended to consolidate for posterity the information about the lavish celebration and spread knowledge of its course of events among magnates and gentry.
The Triumph of Taida Announced. On the Diary of Investiture of Teofila Wiśniowiecka at the Dominican Order in Lvov in 1753
Keywords: literatura okolicznościowa; diariusz obłóczyn; obłóczyny; Teofila Wiśniowiecka; lwowskie dominikanki; kaznodziejstwo; occasional literature; diary of investiture; investiture; Teofila Wiśniowiecka; the Dominicans in Lvov; preaching